Lipid metabolism disturbances contribute to insulin resistance and decrease insulin sensitivity by malathion exposure in Wistar rat. (April 2015) - Lasram, Mohamed Montassar; Bouzid, Kahena; Douib, Ines Bini; Annabi, Alya; El Elj, Naziha; El Fazaa, Saloua; Abdelmoula, Jaouida; Gharbi, Najoua
Abstract Several studies showed that organophosphorus pesticides disturb glucose homeostasis and can increase incidence of metabolic disorders and diabetes via insulin resistance. The current study investigates the influence of malathion on glucose metabolism regulation, in vivo, during subchronic exposure. Malathion was administered orally (200 mg/kg), once a day for 28 consecutive days. Plasma glucose, insulin and Glycated hemoglobin levels were significantly increased while hepatic glycogen content was decreased in intoxicated animals compared with the control group. Furthermore, there was a significant disturbance of lipid content in subchronic treated and post-treated rats deprived of malathion for one month. In addition, we used the homeostasis model assessment (HOMA) to assess insulin resistance (HOMA-IR) and pancreatic β-cell function (HOMA-β). Our results show that malathion increases insulin resistance biomarkers and decreases insulin sensitivity indices. Statistical analysis demonstrates that there was a positive and strong significant correlation between insulin level and insulin resistance indices, HOMA-IR, HOMA-β. Similarly, a negative and significant correlation was also found between insulin level and insulin sensitivity indices. For the first time, we demonstrate that malathion induces insulin resistance in vivo using homeostasis model assessment and these changes were detectable one month after the end of exposure. To explain insulin resistance induced by malathion we focus on lipid metabolism disturbances and their interaction with many proteins involved in insulin signaling pathways.